EVALUASI PROGRAM E-LEARNING BERBASIS KNOWLEDGE MANAGEMENT SYSTEM (KMS) DI ST JOSEPH INTERNATIONAL PRIMARY SCHOOL JAKARTA (EVALUASI PROGRAM DENGAN MENGGUNAKAN MODIFIKASI MODEL HAMMOND) - APRILIANA APRILIANA (Jurnal Evaluasi Pendidikan, 2019)
This program evaluation study was conducted to measure the effectiveness of e-learning program in ST. Joseph Primary School Jakarta using modified Hammond model dengan cuu. The purpose of implementing e-learning in ST. Joseph Primary School Jakarta is to increase students’ positive perceptions of learning, increasing students' understanding of learning materials, and the satisfaction of students and parents towards the use of the program. The research method used is qualitative method. Quantitative datas from questionnaires were analyzed using descriptive statistics. While the qualitative method is used to obtain a description of the program implementation related to the success and obstacles experienced during the implementation of the E-Learning Program Based on Knowledge Management System in ST. Joseph Primary School Jakarta. The evaluation study of this program uses a modified Hammond model by adding technology in the existing 3 dimensions. There are four components of evaluation area: (1) Instruction Dimension, (2) Institutional Dimension, (3) Behavior Dimension and (4) Technology Dimension. The result of this study concluded that the overall dimensions evaluated have been in accordance with the predefined evaluation criteria.The recommendation given to the policy holder is to continue the E-Learning Program Based on Knowledge Management System in ST. Joseph Primary School Jakarta with some improvements to be made in areas that have not met the standard criteria.